Simulation-based ultrasound-guided central venous cannulation training program - Denadai, Rafael; Toledo, Andreia Padilha; Bernades, Danielle Milani; Diniz, Felipe Daldegan; Eid, Fernanda Brandão; Lanfranchi, Livia Maria Marcondes de Moura; Amaro, Luciana Chamone; Germani, Natalia Mariana; Parise, Vinicius Gutierrez; Filho, Claudio Nascimento Pacheco; Saad-Hossne, Rogério [UNESP] (FapUNIFESP (SciELO), 2014)
PURPOSE: To propose a simulation-based ultrasound-guided central venous cannulation skills' training program, during residency.METHODS: This study describes the strategies for learning the ultrasound-guided central venous cannulation on low-fidelity bench models. The preparation of bench models, educational goals, processes of skill acquisition, feedback and evaluation methods were also outlined. The training program was based on key references to the subject.RESULTS: It was formulated a simulation-based ultrasound-guided central venous cannulation teaching program on low-fidelity bench models.CONCLUSION: A simulation-based inexpensive, low-stress, no-risk learning program on low-fidelity bench models was proposed to facilitate acquisition of ultrasound-guided central venous cannulation skills by residents-in-training before exposure to the living patient.
Keywords: Education; Interventional; Learning; Models, educational; Residency; Surgery; Teaching materials; Ultrasonography; Vascular access devices